Mapping the Research Output of the Journal ’Strategic Studies’- Islamabad: A Statistical Review - Abid Hussain, Saeed UllaH jAn (IJoLIS, 2024)
Purpose: To extract and scrutinize the published data of the Institute of Strategic Studeis Islamabad (ISSI) TITLE Strategic Studies".